HUBUNGAN BILATERAL INDONESIA-RUSIA DI BIDANG MILITER: Sebuah Pembahasan Dalam Perspektif Global (2004-2014) - Fermana, Robby Ilma (2016)
This research entitled "Indonesia-Russia Bilateral Relations in Military Affairs: A Discussion In a Global Perspective (2004-2013)". The main problems concerns the research, Why Indonesia choose Russia as a partner in the military on 2004-2013? The main problem developed into three research problem, those are: (1) How was the relationship of dynamic bilateral between Indonesia-Russia in military on 2004-2013? (2) How was the realization of Indonesia-Russia bilateral military relationship on 2004-2013? (3) How were constraints faced by Indonesia-Russia bilateral military relationship on 2004-2013? In addition, there are some aims of studies that the authors set the goal of which, describing the relationship of dynamic bilateral between Indonesia-Russia in the military on 2004-2013. Which covers, military cooperation between Indonesia and Russia in "Orba" government until "Reformasi" on 2004-2013. To explaining the realization of Indonesia-Russia in bilateral military relationship on 2004-2013, include agreements agreed between both parties, the Indonesian government's efforts to modernize the country's defense industry in an effort to reduce dependence on the United States. Describing the constraints faced by Indonesia in bilateral military relations with Russia on 2004-2013. The research method used in this study is historical method in which it is a way to know the history by using interdicipliner approach of internasioal relationship include deterrence and balance of power. The steps of the research historical method cover the choice of research topics, heuristics, criticism of sources, interpretation and historiography. Based on the research findings, it can be concluded that the relationship Indonesia-Russia bilateral military caused by two conditions (1) A state of imbalance lack of military strength in the Asia Pacific region causes an under security dilemma that will effect region these countries to increase military strength, especially for Indonesia. (2) Alutsista Indonesia can not be used in full, due to the US embargo implement policies on human rights violations committed in Dili, East Timor in 1992. Moreover Russia is selected as a partner military because of competitively military weapons technology which almost comparable with Europe and the United States. In bilateral military cooperation with Russia also does not give elaborate prerequisites for Indonesia. Bilateral cooperation in the military with Russia, in the purchase of armaments with the transfer of technology, such as appropriate training with weapons purchased and training of technical personnel weapons, also in pyment weapons could yield joint production. In terms of foreign policy of Russia has experienced a change which is open for any country in a state of multipolarity, while foreign policy of Indonesia is a "bebas aktif" politics. The focus of this study to bilateral cooperation in the military field during President Susilo Bambang Yudhoyono.--------------Skripsi ini berjudul "Hubungan Bilateral Indonesia-Rusia Di Bidang Militer: Sebuah Pembahasan Dalam Perspektif Global (2004-2014)". Permasalahan utama yang menjadi keresahan peneliti, yaitu Mengapa Indonesia memilih Rusia sebagai mitra kerjasama dalam bidang militer periode 2004-2014? Permasalahan tersebut dikembangkan menjadi tiga pertanyaan rumusan masalah yaitu: (1) Bagaimana dinamika perjalanan hubungan bilateral Indonesia-Rusia dalam bidang militer periode 2004-2014? (2) Bagaimana realisasi hubungan bilateral Indonesia-Rusia dalam bidang militer periode 2004-2014? (3) Bagaimana kendala yang dihadapi Indonesia-Rusia dalam hubungan bilateral dalam bidang militer pada periode 2004-2014? Selain itu, ada beberapa tujuan penelitian yang penulis tetapkan diantaranya, Mendeskripsikan dinamika perjalanan hubungan bilateral Indonesia dengan Rusia dalam bidang militer pada periode 2004-2014, meliputi hubungan kerjasama militer Indonesia dengan Rusia masa pemerintahan Orba sampai masa Reformasi tahun 2004-2014. Mendeskripsikan realisasi hubungan bilateral Indonesia dengan Rusia dalam bidang militer pada periode 2004-2014, meliputi kesepakatan-kesepakatan yang disetujui antara kedua belah pihak, upaya pemerintah Indonesia untuk memodernisasi persenjataan dan industri pertahanan dalam negeri sebagai upaya mengurangi ketergantungan terhadap Amerika Serikat. Mendeskripsikan kendala yang dihadapi Indonesia dalam hubungan bilateral dengan Rusia di bidang militer pada periode 2004-2014. Metode yang digunakan dalam penelitian ini adalah metode historis dengan menggunakan pendekatan interdisipliner dari ilmu hubungan internasional deterensi dan balance of power, tahapan-tahapan historis yaitu pemilihan topik penelitian, heuristik, kritik sumber, interpertasi dan historiografi. Berdasarkan dari hasil temuan penelitian didapatkan hubungan bilateral Indonesia-Rusia di bidang militer yang disebabkan dua kondisi (1) Keadaan ketidakseimbangnya kekuatan militer di kawasan Asia Pasifik yang menyebabkan sebuah dilema keamanan yang nantinya negara-negara dikawasan melakukan peningkatan kekuatan militer khususnya bagi Indonesia. (2) Alutsista Indonesia tidak dapat digunakan secara penuh, dikarenakan Amerika Serikat menerapkan kebijakan embargo persenjataan atas pelangaran HAM yang dilakukan di Dili Timor-Timur pada tahun 1992. Lebih lanjut Rusia dipilih sebagai mitra kerjasama karena secara kompetitif teknologi persenjataan militer hampir sebanding dengan Eropa maupun Amerika Serikat. juga Rusia tidak memberikan prasyarat yang rumit bagi negara Indonesia dalam kerjasamanya bilateral dibidang militer. Pembelian persenjataan dengan Rusia disertai dengan transfer teknologi, seperti pelatihan-pelatihan yang sesuai dengan persenjataan yang dibeli dan pelatihan tenaga teknik persenjataan. Juga, dalam pembayaranya persenjataan dilakukan dengan sistem imbal dagang. Dari segi kebijakan politik luar negeri Rusia sudah mengalami perubahan yang bersifat terbuka bagi negara manapun dalam keadaan multipolaritas ini, sedangkan kebijakan politik luar negeri Indonesia adalah politik bebas aktif. Fokus penelitian ini mengenai hubungan kerjasama bilateral dalam bidang militer pada masa Presiden Susilo Bambang Yudhoyono.